Personality Trait and Cyber Affair in Young Adults’ Romantic Relationship: Relationship Satisfaction as Moderator (Universitas Muhammadiyah Metro, 2023)
A cyber affair is an affair in the form of emotional or sexual, carried out through virtual contacts. Cyber affair has various factors, including personality traits and relationship satisfaction. This study aims to determine the role of relationship satisfaction as a moderator of the relationship between personality traits and cyber affairs in young adult dating individuals. This study uses three measurements: Social Media Infidelity-Related Behavior, IPIP-BFM-25 dimensions of extraversion, agreeableness, conscientiousness, and Relationship Assessment Scale. The sampling technique used was convenience sampling, with 734 participants obtained. Statistical analysis includes descriptive statistics, correlations, covariates, and moderation to answer the research questions. As a result, the conscientiousness personality trait has a significant negative correlation with cyber affairs. Moderation analysis indicates no moderating effect of relationship satisfaction on the relationship between personality traits and cyber affairs. It is thought to be caused by a reduced correlation between personality traits and cyber affairs due to the influence of relationship satisfaction.